Macromol. Rapid commun. 19/2014. - Montrikittiphant,T; Tang,M; Lee,KY; Williams,CK; Bismarck,A (Macromol Rapid Commun, 2014)
Frontispiece: A Werkstoffverbund (laminated composite) manufacturing concept is used to produce high performance renewable bacterial cellulose (BC) nanopaper reinforced thermoplastic laminates. The mechanical performance of the resulting BC-reinforced thermoplastic laminates is found to be dependent on the tensile performance of the reinforcing BC nanopaper. Further details can be found in the article by T. Montrikittiphant, M. Tang, K.-Y. Lee, C. K. Williams, and A. Bismarck on page 1640.